Pengaruh Faktor-Faktor Motivasi Terhadap Kinerja Karyawan - Tho, Ivone (Fakultas Ekonomi, UIN Maliki Malang, 2010)
The mission this research to make analysis about the effect of motivation factors that concists of income, environment of work, connected between labours, award, and promotion of profession, towards to performance of labour in Kabupaten Fak-fak, the second mission analized between this variables, what are dominant variables towards to performance of labour. The first hypothesis reallty, that is there are significant effect between motivation variables that consists of income (X1), environment of work (X2), connected between laboursÂ (X3), awards (X4), and promotion of profession (X5), towards to performance of labour in Kabupaten Fak-fak. Between that five variables have two variables that have significant effect that is X3, and X4 and then there arenâ€™t three significant variables that is X1, X2, dan X5. And then for the second mission in this research that want to know that award variable (X4) is motivation variables that have effect dominant variable towards to performance of labour in Kabupaten Fak-fak.